Photocatalytic inactivation of Clostridium perfringens and coliphages in water - Guimarães,J.R. (2003)
This study presents results of the photocatalytic inactivation of two groups of microorganisms: spores of the anaerobic bacterium Clostridium perfringens and coliphage. A cylindrical reactor impregnated with titanium dioxide and irradiated with ultraviolet light (15 W) was used. Parameters such as color, turbidity, hydraulic detention time (HDT) and initial concentration of microorganisms were evaluated in relation to the efficiency of the inactivation process. According to the experiments with the bacterium C. perfringens, the reduction in number of microorganisms was higher than 98% after an irradiation time of 152 seconds, independent of color and turbidity. For solutions with low turbidities efficiency of the coliphage inactivation reached approximately 100% between 89 and 104 HDT, while this value was 98% for solutions with higher turbidities.